Masuk Melayu Menegosiasikan Islam dan Kemelayuan di Malaysia - Steve G. Chr. Gaspersz (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2017)
This paper elaborates the construction of religious identity (Islam) and ethnicity (Malay)through ideological concept „Masuk Melayu‟ (lit. „becoming Malay‟) in Malaysia. Theintertwined religion and ethnicity bring about political notion and practice which combine bothas an ideology of political culture in Malaysia. The ideology has been used as a parameter tomanage political and societal life with the multicultural characteristic in Malaysia. It alsodemonstrates that the construction of religious identity and ethnicity in Malaysia, as well asother Southeast Asia countries, generally might not be separated from colonialism discourseoccurred in the past. Colonialism had inherited socio-cultural and political systems by which,then, become the foundation of governmental bureaucracy activity and the establishment of apolitical culture of Southeast Asia societies until today. The postcolonial government inMalaysia, however, has been continuing such construction of identity by adding contextualpolitical meaning and practice innovatively to maintain and sustain their political power.Masuk Melayu is an arena for negotiating political power by injecting religious identity ofIslam as a powerful political axis in Malaysia.